Student performance evaluation using fuzzy analytic hierarchy process (FAHP) with VIKOR method / Ahmad Hisyamuddin Abd Rahman ... [et al.] - Abd Rahman, Ahmad Hisyamuddin; Ahmad, Noraini; Hassanuddin, Nor Aini; Mohd Yusof, Zanariah (2020)
Evaluation of student academic performance is most relevant to the tertiary institution in order to obtain a high reputation and rank position as compared to others. Essentially, the performance of students has been considered excellent or not solely based on academic result. Nonetheless, there are few colleges that defined good student based on student's performance over other accomplishments. In this study, the student performance was evaluated based on student's academic result and their involvement in university activities. Therefore, the Fuzzy Analytic Hierarchy Process and VIKOR method, a decision-making instrument was constructed in this project that focuses on the selection process to calculate and to rank the most successful student in the university. In this research, three important main criteria and several subcriteria have been considered. The main criteria are academic, club involvement and participation. The weighting of each criterion and sub-criteria were calculated by using the Fuzzy Analytic Hierarchy Process (FAHP) method. The results were ranked by using Vlse Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR method). Based on the results the student who has the lowest value of Qi will be at the top ranking of student's performance and the highest value of Qi will be at the bottom ranking based on VIKOR method.